Light Intensity Affects Dry Matter, Photosynthesis and Chlorophyll Fluorescence of Oriental Lily - Zhang, Ya Juan; Xie, Zhong Kui; Wang, Ya Jun; Su, Pei xi; An, Li Ping; Gao, Hong (2011)
Oriental lily (Lilium auratum L. cv. Sorbonne) plants were grown under four light intensities (0%, 60%, 75% and 80% shade) in China's Horqin Sandy Land and their photosynthetic ability, dry matter production and chlorophyll fluorescence were determined. There was higher dry matter in the bulbs, stems and whole plant of lily cultivated in the shade. 'Mid-day depression' of photosynthesis occurred in the 0% shade treatments, indicating that excessively high light intensity could decrease photosynthesis. The transpiration rate (E) values of plants in the 80% shade treatment were higher than those in the unshaded, but their stomatal conductance (P n) and water use efficiency (WUE) values were comparatively lower. This result suggests that low light intensity can also decrease photosynthesis. Both stomatal and non-stomatal limitations to photosynthesis were observed under shade and unshaded conditions based on changes in P n , stomatal conductance (g s) and intercellular CO 2 concentration (C i). The low maximum fluorescence (F M), variable fluorescence (F V) and maximum photosystem II (PSII) photochemical efficiency (F V /F M) under full sunlight suggested that excessive sunlight could damage the plant's photosynthetic apparatus. This may be due to damage to PSII, resulting in photoinhibition when lily is cultivated under high light intensities. To increase the commercial value of Oriental lily, approximately 75% shade appeared to be optimal.
Keywords: Lilies; Chlorophyll; Photosynthesis